Style and Ethics of Communication in Science and Engineering - Humphrey, Jay D.; Holmes, Jeffrey W. (Synthesis Lectures on Engineering,, 2009)
Scientists and engineers seek to discover and disseminate knowledge so that it can be used to improve the human condition. Style and Ethics of Communication in Science and Engineering serves as a valuable aid in this pursuit-it can be used as a textbook for undergraduate or graduate courses on technical communication and ethics, a reference book for senior design courses, or a handbook for young investigators and beginning faculty members. In addition to presenting methods for writing clearly and concisely and improving oral presentations, this compact book provides practical guidelines for preparing theses, dissertations, journal papers for publication, and proposals for research funding. Issues of authorship, peer review, plagiarism, recordkeeping, and copyright are addressed in detail, and case studies of research misconduct are presented to highlight the need for proactive attention to scientific integrity. Ample exercises cause the reader to stop and think. Style and Ethics of Communication in Science and Engineering thus motivates the reader to develop an effective, individual style of communication and a personal commitment to integrity, each of which are essential to success in the workplace. Table of Contents: Motivation / Writing Well / Scientific Publications / Proposals and Grant Applications / Oral Communication / Authorship / Recordkeeping / Ownership of Ideas, Data, and Publications.